Enteric-coated mycophenolate sodium in psoriasis vulgaris: an open pilot study. (February 2014) - Fallah Arani, Shiva; Waalboer Spuij, Rick; Nijsten, Tamar; Neumann, H. A. Martino; Thio, Bing
<x xml:space="preserve">Abstract</x> Background: Mycophenolate mofetil is a well-known immunosuppressive agent in transplantation medicine. The efficacy of enteric-coated mycophenolate sodium (EC-MPS) was confirmed in other inflammatory skin diseases, including atopic dermatitis and SCLE. Objective: To investigate the efficacy and the tolerability/short-term safety of EC-MPS in patients with moderate to severe chronic plaque psoriasis. Patients and methods: An open-label pilot study in which 20 patients with a PASI >10 received EC-MPS 720 mg twice daily for 6 weeks followed by 360 mg twice daily for another 6 weeks. Patients who completed 12 weeks of treatment were followed-up for an additional 12 weeks. Treatment outcomes were assessed with PASI50% and PASI75%. Results: Eighteen men and two women (mean age 46 years) entered the study. Sixty-five percent (13/20) finished the treatment period. By week 6, no patient achieved PASI 75% and 8/20 patients achieved a PASI 50%. Compared to week 6, 4/13 showed a deterioration of their psoriasis at week 12. Twenty-five percent (2/8) achieved a PASI 75% in week 24. The most-reported adverse events were itching (30%), diarrhea (10%), and a reversible elevation of the triglycerides level. Conclusion: EC-MPS does not seem effective as monotherapy for moderate to severe psoriasis, but might be used at a dosage of 1440 mg daily in well-selected patients with treatment-resistant psoriasis.